Metropolizacijos procesai ES teritorinio planavimo doktrinoje ir Lietuva - Vanagas, Jurgis (Journal of Architecture and Urbanism, 2007)
Processes of metropolization in the territory planning doctrine of the EU and Lithuania The paper is devoted to the analysis of the main con- temporaty notions of metropolization in the doctrine of the EU, its development, pluses and minuses and to the consideration of the present processes taking place in this respect in modern- day Lithuania. In the beginning the author widely points to the main terms, such as metropolis, region metropolitan region, and shortly reviews the history of the EU, its territory planning principles. He reveals the early roots of these conceptions found in the works of utopian thinkers – Sir Thomas More, Robert Owen – productively continued in the territory planning blueprints of the19th century accomplished by A. Soria у Mata and E. Howard. An important stage of modern regional planning, paving the way to the later EU steps in this sphere, were wide-scale planning projects of the early decades of the 20th century and especially post-war regional programmes like Great London development. All these achievements of the past in regional planning enabled to arrive at an idea of uniting efforts on a European scale which took place in 1970 and to proclaim the Europe’s Regional Planning Chart seventeen years later. The prominent Maastricht Treaty signed in 1992 finally balanced the interests of the whole Europe and laid down the fundamentals of its “common home”. The regional situation in Lithuania, as in all the new EU member states, is rather multipartite. Its greatest drawback is lack of its own representative in the highest echelon of the Baltic Sea Region urban categories – in the composition of cities officially included into the list of the so-called european Cities. This status provides the most prestigious situation and evident advantages in the international urban network as well as in the intercon- nectional relations and cooperation of the largest metropolies. Eventually the grade of euro City presents as if an important “gate” to the wide field of various beneficial actions overgrowing national borders. The author reports his position towards Lithuania’s abilities “to delegate” its representative to the top of the BSR city hierarchy. According to the arguments given in the paper, an exclusive chance to achieve this international appreciation is through employing a unique and unprecedented situation of the country, namely, existence of the twin cities of Vilnius and Kaunas, similarity of their size and typological feature, their close many-sided cooperation, distinction by intensive oncoming commuting flows and so on. Studies of labour market show that in this spontaneous urban belt a qualitatively new model of “job-residing” location comes into being: to settle in one city and to work in the other one. Together with improving communication between these cities and mounting traffic rate, this process will certainly flourish. By a reasonable regulation and stimulation of these spontaneous processes, a great combined metropolitan unit (“dipolis”) containing Vilnius and Kaunas can be formed. Inexorable processes of globalization definitively stimulate necessity to shake-up local and national economies, to revise essentially inveterate principles of territory planning. Processes taking place globally within the last decades show unceasing trends to join cities, towns and townships network into united polycentral or bipolar systems along the main communication channels. A model of concentrated location of urban units (as the opposite to their geographically dispersed, gradually developed network suggested by W.Christaller) seems to be more rational and advantageous in numerous aspects. Therefore, resuming all these considerations, a new essential question arrises: is the idea of sustainable development formulated in 1987 by Gro Harlem Brundtland the only and undisputed alternative in territorial development? Article in Lithuanian. Santrauka. Peržvelgiama Europos Sąjungos sukūrimo chronologija, jos teritorinio planavimo doktrinos ištakos, pagrindiniai Europos „bendrųjų namų“ pamatus padėjusios Mastrichto sutarties teiginiai. Atskleidžiamos šiuolaikinių globalizacijos procesų stimuliuojamų didelių metropolinių regionų formavimosi procesų priežastys. Pritariama vis dažniau pasigirstančioms abejonėms, ar kelis dešimtmečius vyravusios darniosios plėtros samprata teritorinio planavimo procese yra vienintelė ir nenuginčijama alternatyva. Šiuo požiūriu Baltijos jūros regiono ir nusistovėjusių teritorinių struktūrinių vienetų (NUTS ) kontekste Lietuva stoko ja ryškaus urbanistinio centro, galinčio pretenduoti į oficialiai pripažintų European City rango miestų sąrašą. Vienintelė galimybė tokiam metropoliniam centrui sukurti – tai Lietuvos Respublikos teritorijos bendrajame plane numatytas Vilniaus ir Kauno potencialų sujungimas. Reikšminiai žodžiai: metropolis, regionas, metropolinis regionas, Euro City, NUTS , dvimiestis, darnioji plėtra. First published online: 21 May 2013